Implementation and sustainability study of a patient’s own medications management policy in the hospital using the RE-AIM framework - Christophe Lelubre; Sophie Lorent; Camille Hoornaert; Stéphanie Pochet; Larissa Zubryckyj (BMJ Open Quality)
Objective The main objective was to develop a policy for the management of patients’ own medications (POM) in a tertiary university hospital and to evaluate the outcomes of its implementation. The secondary objective was to explore the effects of introducing a policy on the incidence and severity of drug-related problems (DRPs).Methods The implementation evaluation was based on the mixed method using the RE-AIM model (reach, effectiveness, adoption, implementation and maintenance). Each POM was analysed to identify the cause and severity of the DRP (pre-implementation and after 1 week, 3 months and 1 year). Three months after the implementation, an interview with hospital providers explored barriers and facilitators of the POM management policy as well as factors impacting the programme’s sustainability.Results 205 patients were included pre-implementation, and over the three post-implementation periods, a total of 586 additional patients were included in the quantitative study. 17 interviews were conducted. Approximately 60% of the included patients brought their POM to the hospital during each period (reach). There was a statistically significant decrease in the percentage of POM self-administered (p<0.001), the percentage of POM used by nurses to administer doses (p<0.001), the rate (p=0.005) and severity (p=0.008) of DRP when compared with the situation before and after 1 week and 3 months of policy implementation (effectiveness, implementation). The rate (p=0.074) and severity (p=0.062) of DRP decrease after 1 year of policy implementation was not significant (maintenance).Conclusions This study presents a POM management policy and highlights the unique challenges of implementing and, in particular, maintaining it in the hospital setting. A POM management policy reduces the incidence and severity of DRP caused by POM if the policy is fully communicated and staff are appropriately trained.